Procedural Path Dependence: Discrimination and the Civil-Criminal Divide - Julie C. Suk (Washington University Law Review, 2008)
Procedural path dependence occurs when the particular features of the procedural system that is charged with enforcing a given legal norm determine the substantive path of that norm. This Article shows how the limits of employment discrimination law in two different national contexts can be explained by procedural dynamics. In France, as in several European countries, employment discrimination law is enforced predominantly in criminal proceedings. French criminal procedure enables the discovery of information necessary to prove the facts of discrimination, whereas the limits of French civil procedure make it impossible for such information to be revealed. As a result, the substantive legal norm of nondiscrimination is being developed in French criminal law, in which the element of intent and the defendant’s strong presumption of innocence are essential. In the United States, liberal civil procedure rules permit the broad discovery of information relevant to proving discrimination. At the same time, the civil litigation system has undermined the law’s adaptability to the evolving social practices that threaten equal employment opportunity. The civil dimension of this procedural system, deeply rooted in the paradigm of the private damages action, tends to favor the employment discrimination claims that most closely resemble torts, thereby limiting the law’s ability to address the complex causes of unequal employment opportunity. This, too, is an example of procedural path dependence. These examples reveal that discrimination is neither criminal nor civil in nature. To overcome its present limits, antidiscrimination law must transcend the substantive principles that have become entrenched by the procedural systems in which it developed.
Keywords: Discrimination in employment; Discrimination in employment -- United States; Comparative law